GAMBARAN INSOMNIA PADA REMAJA DI SMK NEGERI 2 PEKANBARU - Raudhatul Zahara; Sofiana Nurchayati; Woferst Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Insomnia became part of sleep disorder which happen mostly in adolescent. The aim of this research was to know the description of insomnia in adolescent with descriptive design. The research used proportionate random sampling involucing 94 students that were selected based on inclusion and exclusion criteria by Insomnia Severity Index (ISI) questionaire. The univariat analysis was attached to determine the frequency distribution  and it showed thet 42 (44,7%) were 17 years old and 70 (74,5%) people were male, the difficulty started to sleep component were 30 people (31,9%), the difficulty to maintained sleep component were 34 people (36,2%), early wake up component were 27 people (28,7%). The satisfaction sleep component were 41 people (43,6%), the effect of sleep problem component were 43 people (45,7%), the anxiety about sleep problem component were 31 people (33,0%), the effect of sleep problem in daily activity were 34 people (36,2%) and the description of insomnia was majority in minor insomnia for 43 people (45,75%). It was recommended to adolescent to increased the sleep quality.  Keywords   : Adolescent, Insomnia, Insomnia Severity Index (ISI)